Pentoxifylline effects on capacitation and fertility of stallion epididymal sperm - Guasti, P. N. [UNESP]; Monteiro, G. A. [UNESP]; Maziero, R. R. D. [UNESP]; Carmo, M. T. [UNESP]; Dell'Aqua, J. A. [UNESP]; Crespilho, A. M.; Rifai, E. A.; Papa, F. O. [UNESP] (Elsevier B.V., 2017)
The aims of this study were to determinate whether pentoxifylline (PTX) increases the motion parameters of fresh and frozen-thawed equine epididymal spermatozoa, to evaluate the tyrosine phosphorylation of frozen-thawed epididymal sperm in the presence of PTX and to determine whether the PTX-treatment of stallion epididymal sperm prior to freezing improves the fertility response of mares to a reduced number of spermatozoa per insemination dose. Fifty epididymis were flushed with a skim milk based extender with or without PTX. The pre-treatment with PTX enhanced the sperm motility after being harvested (P<0.05); however the freeze-thaw process did not alter the sperm kinematics between control and treated samples (P>0.05). Plasma membrane integrity did not differ between control and PTX group after recovery and after thawing (P>0.05), as observed in tyrosine phosphorylation, which the PTX treatment did not alter the percentage of tail-associated immunofluorescence of cryopreserved epididymal sperm (P>0.05). For the fertility trial, different insemination groups were tested: 800 x 10(6) epididymal sperm (C800); 100 x 10(6) epididymal sperm (C100); 100 x 10(6) epididymal sperm recovered in an extender containing PTX (P1X100). The conception rates for C800; C100 and PTX100 were 68.7% (11/16); 31.5% (5/16) and 50% (8/16), respectively. The conception rate did not differ among groups (P>0.05), however, a low number of animals was used in this study. A trend toward significance (P=0.07) was observed between C800 and C100 groups. In conclusion, PTX has no deleterious effect on sperm motility, viability and capacitation of cryopreserved stallion epididymal sperm. The conventional artificial insemination with 100 x 10(6) sperm recovered with PTX ensures acceptable conception rates and maximize the limited number of doses of cryopreserved stallion epididymal sperm. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Cauda epididymal sperm; Epididymis; Flushing extender; Tyrosine phosphorylation; Insemination dose